2021
DOI: 10.1111/1748-8583.12392
|View full text |Cite
|
Sign up to set email alerts
|

The influence of human resource management systems on employee job crafting: An integrated content and process approach

Abstract: Although job crafting has many beneficial outcomes for organisations, research on the antecedents of this behaviour is lacking. Through a two-wave study including 87 managers and 342 employees of nine Chinese firms, an integrated content and process model of human resource management (HRM) systems is developed and used to demonstrate that HRM systems have a crucial influence on employee job crafting. The results of multilevel structural equation models reveal that implemented HRM systems can increase employee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Previous research has shown that individual characteristics, including gender, anxiety, and hierarchical rank, as well as organizational characteristics such as acquisition, serve as antecedents of advice-seeking [ 51 , 52 , 53 , 54 ]. In addition, it has been found that growth needs and creative self-efficacy as individual characteristics, job autonomy as job characteristics, and organizational support and human resource management systems as organizational characteristics positively influence task crafting [ 55 , 56 , 57 , 58 ]. However, prior studies have neglected to investigate the phenomenon that organizational members are exposed to ambiguous roles due to changes in work context and the effects of these ambiguous roles on advice-seeking and task crafting.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that individual characteristics, including gender, anxiety, and hierarchical rank, as well as organizational characteristics such as acquisition, serve as antecedents of advice-seeking [ 51 , 52 , 53 , 54 ]. In addition, it has been found that growth needs and creative self-efficacy as individual characteristics, job autonomy as job characteristics, and organizational support and human resource management systems as organizational characteristics positively influence task crafting [ 55 , 56 , 57 , 58 ]. However, prior studies have neglected to investigate the phenomenon that organizational members are exposed to ambiguous roles due to changes in work context and the effects of these ambiguous roles on advice-seeking and task crafting.…”
Section: Discussionmentioning
confidence: 99%
“…With the regard to job crafting literature, it is important to note that research so far has dedicated much attention to individual antecedents, overlooking the contextual and socioenvironmental conditions that may enable job crafting behaviors (Buonocore et al, 2020;Hu et al, 2021;Huyghebaert-Zouaghi et al, 2021;Park and Park, 2021;Yoon et al, 2019). Our study shows that uncertainty can generate a motivational boost in stimulating proactive behaviours in order to increase a perception of fit in the workplace (Tims et al, 2016).…”
Section: Discussionmentioning
confidence: 76%
“…Petrou et al, 2017Petrou et al, , 2018. Moreover, our study contributes to advancing prior research on the antecedents of job crafting (Buonocore et al, 2020;Hu et al, 2021;Huyghebaert-Zouaghi et al, 2021;Yoon et al, 2019), by exploring how perceptions of uncertainty can influence job crafting behaviors (Barclay et al, 2022;Chen and Tang, 2021). Finally, using a qualitative approach in the study of job crafting is an important methodological advancement, as research on the topic is predominantly quantitative (Zhang and Parker, 2019), therefore unable to provide in-depth insights into the process underlying the adoption of these proactive behaviors (Lazazzara et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…However, our findings highlight the importance of creating the conditions that can encourage promotion ‐oriented job crafting behaviors because these behaviors are more likely to foster employee well‐being. Importantly, recent evidence suggests that the perceived presence of human resource management systems can be a key factor promoting job crafting behaviors because this may provide additional resources that can encourage employees to engage in these behaviors (Hu et al, 2021). This suggests that SHRM has a key role to play in creating the circumstances that promote job crafting.…”
Section: Discussionmentioning
confidence: 99%